Automation risk along individual careers: Static and dynamic upgrades in cities - László Czaller; László Eriksson; Balázs Lengyel (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
Automation risk of workers prevails less in large cities compared to small cities, but little is known about the drivers of this emerging urban phenomenon. We examine the role of cities on changes in automation risk through individual careers of workers by separating labour mobility to a city from labour mobility within a city. Applying panel data representing all Swedish workers from 2005 to 2013 we provide new evidence that working in, or moving to, metropolitan areas lower automation risk of workers. We find that high-skilled workers enjoy dynamic occupation upgrades in cities and benefit from accumulating experience in the urban labour market, while low-skilled workers experience a single static upgrade when moving to a city.
Keywords: J23; J24; J62; R23; 330; automation risk; metropolitan regions; career upgrade; labour mobility